IMPLIKASI KERUSUHAN 1999 TERHADAP INTERAKSI SOSIAL KEAGAMAAN ETNIS MELAYU DAN MADURA DI KALIMANTAN BARAT - Syukron Wahyudhi (UIN Sunan Kalijaga Yogyakarta, 2019)
Indonesia is a country that has diversity of ethnicities and religions. The diversity makes Indonesia known as a multicultural nation. However, the plurality that is rooted in them does not always lead to good. It is West Kalimantan, one of some regions that has a bitter history because it has repeatedly experienced ethnic violence. This theme is important to be researched for conflict is part of the human civilization history. If the conflict can be managed well, it will make both territory and society being grown up. But when conflict comes to violence and even murder, it becomes a historical wound that is hard to wiped out. In this research the researcher concentrates on a riot between ethnic Malay and ethnic Madura in 1999. The riot is interesting to be discussed by the researcher bacause the both ethnicities have a same religious background, Islam; even in term of religious culture, it is not much different. This research is a field study using the theory of Bikhu Parekh Multiculturalism. The problem statements in this reasearch are, first, what is the factor in the riot between ethnic Malay and Madura? Second, how are the implications toward socio-religious interaction between the both ethnicities nowadays? From the result of this research, it can be concluded that; First, it is an accumulation of ethnic Malay anger against ethnic Madura which for so long is viewed as often violates traditional and religious norms. Second, the riot becomes historical wound because it is implicated in sentiment and stereotypes between the two ethnic groups. According to the provident researcher, there should be some continuous efforts from the religious and traditional figures of both ethnics group as an endeavor to allay the sentiment and stereotypes in the society, in order to establish the harmony between ethnic Malay and ethnic Madura in Sambas and Singkawang. Keywords: Malay-Madura Riot, Social Interaction, and Multiculturalism.